Association of chronic inflammation with cardiovascular risk in chronic obstructive pulmonary disease—A cross‐sectional study. Issue 3 (7th April 2022) - Ljubičić, Đivo; Balta, Vedran; Dilber, Dario; Vražić, Hrvoje; Đikić, Domagoj; Odeh, Dyana; Habek, Jasna Čerkez; Vukovac, Emilija Lozo; Tudorić, Neven
Abstract: Background and Aims: COPD is progressive lung disease with known higher cardiovascular (CV) risk, mainly attributed to smoking of cigarettes as the main etiological factor of disease. The aim of this study was to compare CV risk in patients with COPD to control groups of smokers and non‐COPD and to investigate the relation of lung function variables, COPD severity, and smoking with Systemic Coronary Risk Estimation (SCORE) risk calculation, arterial stiffness (AS) values, and biological systemic inflammatory markers. Methods: A total of 208 subjects were included in this study: 61 subjects diagnosed with COPD, 83 smokers without COPD, and 64 nonsmokers without COPD. Medical history and clinical data were recorded, including assessment of pulmonary function and AS, calculation of ankle‐brachial index, blood analysis, and CV risk assessment by SCORE risk calculation. Results: Subjects with COPD had significantly higher values of SCORE calculation of risk, central aortic pressure, AS, and markers of systemic inflammation compared to control groups of smokers and nonsmokers without COPD ( p < 0.001). Furthermore, statistically significant increase in hs‐CRP concentration was found between the COPD group and the control group of non‐COPD smokers ( p < 0.001), and a statistically significantly higher SCORE calculation was found in the COPD group compared to control groups of smokers and nonsmokers without COPD ( p < 0.001). Conclusion: The results of the research support further identification and research of biological markers and simple specific tests such as arteriography that will enable progress in personalized treatment of patients with COPD and better primary and secondary prevention of comorbidities with the aim of improved treatment outcome.